Synergy Pattern of Short Cationic Antimicrobial Peptides Against Multidrug-Resistant Pseudomonas aeruginosa - Ruden, Serge; Rieder, Annika; Chis Ster, Irina; Schwartz, Thomas; Mikut, Ralf; Hilpert, Kai (Frontiers in Microbiology, 2019)
With the rise of various multi-drug resistance pathogenic bacteria, worldwide health care is under pressure to respond. Conventional antibiotics are failing and the development of novel classes or alternative strategies is a major priority. Antimicrobial peptides (AMPs) can not only kill multi-drug resistant bacteria, but also can be used synergistically with conventional antibiotics. We selected 30 short AMPs from different origins and measured their synergy in combination with Polymyxin B, Piperacillin, Ceftazidime, Cefepime, Meropenem, Imipenem, Tetracycline, Erythromycin, Kanamycin, Tobramycin, Amikacin, Gentamycin, and Ciprofloxacin. In total 403 unique combinations were tested against a multi-drug resistant Pseudomonas aeruginosa isolate (PA910). As a measure of the synergistic effects, fractional inhibitory concentrations (FICs) were determined using microdilution assays with FICs ranges between 0.25 and 2. A high number of combinations between peptides and Polymyxin B, Erythromycin and Tetracycline were found to be synergistic. Novel variants of Indolicidin also showed a high frequency in synergist interaction.